2015
DOI: 10.1111/jpi.12208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the immunomodulatory effect of melatonin on the T‐cell response in peripheral blood from systemic lupus erythematosus patients

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disorder characterized by the production of antinuclear autoantibodies. In addition, the involvement of CD4+ T-helper (Th) cells in SLE has become increasingly evident. Although the role of melatonin has been tested in some experimental models of lupus with inconclusive results, there are no studies evaluating the melatonin effect on cells from patients with SLE. Therefore, the aim of this study was to analyse the role of in vitro administered melatonin in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 52 publications
1
44
0
3
Order By: Relevance
“…Although melatonin has little effect on Treg cells in vitro or in individuals who have progressed from a metastatic solid tumor, melatonin causes a significant reduction in the number of Treg cells in patients with untreatable metastatic solid tumors . Melatonin does not influence the frequency of Foxp3 + cells in PBMCs from healthy individuals, but augments the number of CD4 + CD3 + Foxp3 + cells in patients with SLE . More importantly, the expression of HIOMT and Foxp3 mRNAs in PBMCs from patients with SLE are positively correlated .…”
Section: Melatonin and Differentiation Of T Cellsmentioning
confidence: 89%
See 1 more Smart Citation
“…Although melatonin has little effect on Treg cells in vitro or in individuals who have progressed from a metastatic solid tumor, melatonin causes a significant reduction in the number of Treg cells in patients with untreatable metastatic solid tumors . Melatonin does not influence the frequency of Foxp3 + cells in PBMCs from healthy individuals, but augments the number of CD4 + CD3 + Foxp3 + cells in patients with SLE . More importantly, the expression of HIOMT and Foxp3 mRNAs in PBMCs from patients with SLE are positively correlated .…”
Section: Melatonin and Differentiation Of T Cellsmentioning
confidence: 89%
“…When the mononuclear cells derived from mouse lymph nodes were stimulated with pMOG in vitro, melatonin significantly decreased the frequency of TNF + CD4 + cells, although it was without effect on the frequencies of IL‐17 + CD4 + and IFN‐γ + CD4 + cells . Melatonin lowers the production IFN‐γ, TNF, IL‐5, IL‐9, and IL‐1β in PBMCs from healthy individuals, although it has almost no effect on production of those cytokines in PBMCs from patients with SLE . Although there are slight differences, the majority of the in vitro investigations suggest that melatonin inhibits Th1 responses, but promotes Th2 responses.…”
Section: Melatonin and Differentiation Of T Cellsmentioning
confidence: 99%
“…Melatonin has been shown to decrease the Treg response in experimental cancer models (Liu et al, 2011) and cancer patients (Vigore et al, 2010). It also increases the in vitro expression of FoxP3, the characteristic Treg transcriptional factor, in peripheral blood mononuclear cells from systemic erythematous lupus patients (Medrano-Campillo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study showed lower daily melatonin concentrations in SLE patients compared to healthy women (14). A recent study showed that melatonin increases the number of T regulatory (Treg) cells expressing FOXP3 and offset BAFF overexpression in SLE patients' cells (15). These findings open a new field of research in SLE that may lead to the use of melatonin as treatment or cotreatment for SLE.…”
mentioning
confidence: 94%